The host response to the probiotic Escherichia coli strain Nissle 1917: Specific up-regulation of the proinflammatory chemokine MCP-1 - Ukena Sya N; Westendorf Astrid M; Hansen Wiebke; Rohde Manfred; Geffers Robert; Coldewey Sina; Suerbaum Sebastian; Buer Jan; Gunzer Florian (BMC, 2005)
Abstract Background The use of live microorganisms to influence positively the course of intestinal disorders such as infectious diarrhea or chronic inflammatory conditions has recently gained increasing interest as a therapeutic alternative. In vitro and in vivo investigations have demonstrated that probiotic-host eukaryotic cell interactions evoke a large number of responses potentially responsible for the effects of probiotics. The aim of this study was to improve our understanding of the E. coli Nissle 1917-host interaction by analyzing the gene expression pattern initiated by this probiotic in human intestinal epithelial cells. Methods Gene expression profiles of Caco-2 cells treated with E. coli Nissle 1917 were analyzed with microarrays. A second human intestinal cell line and also pieces of small intestine from BALB/c mice were used to confirm regulatory data of selected genes by real-time RT-PCR and cytometric bead array (CBA) to detect secretion of corresponding proteins. Results Whole genome expression analysis revealed 126 genes specifically regulated after treatment of confluent Caco-2 cells with E. coli Nissle 1917. Among others, expression of genes encoding the proinflammatory molecules monocyte chemoattractant protein-1 ligand 2 (MCP-1), macrophage inflammatory protein-2 alpha (MIP-2α) and macrophage inflammatory protein-2 beta (MIP-2β) was increased up to 10 fold. Caco-2 cells cocultured with E. coli Nissle 1917 also secreted high amounts of MCP-1 protein. Elevated levels of MCP-1 and MIP-2α mRNA could be confirmed with Lovo cells. MCP-1 gene expression was also up-regulated in mouse intestinal tissue. Conclusion Thus, probiotic E. coli Nissle 1917 specifically upregulates expression of proinflammatory genes and proteins in human and mouse intestinal epithelial cells.